Implementation of coral propagation for coral reef garden in Nusa Dua, Bali. (November 2019) - Ampou, E E; Hutasoit, P; Janetski, N; Yusuf, S; Damar, A; Petta, C; Hutahaean, A A
Abstract: MARRS ( Mars Assisted Reef Restoration System ) is an artificial reef method that resembles spider webs and has been implemented in several regions of Indonesia, including Samuh beach, Nusa Dua, Bali. Since July - October 2018, 761 MARRS units, supporting a total of ± 10, 600 coral fragments, have been installed. The aim of this research is to provide an initial investigation into establishing a mini-coral reef park in Indonesia. Monitoring was done by identifying habitat geomorphology methods with photo transects and coral propagation status in MARRS using the random visual census method. From the process of habitat geomorphology classification in the artificial reef network, there were 9 types of habitat classified on the fringing reef, reef flats and fore reefs. Ten hard coral species from the Scleractinia group were identified from 10 randomly-selected and monitored MARRS units: Acropora formosa, A. hyacinthus, Pocillopora verucosa, P. damicornis, Psammocora sp., Symphyllia sp., Stylophora pistillata, Turbinaria sp., Echinopora sp. and Favites sp . Three significant coral factors were found to be present within the coral propagation system: resistance, competition and predators.